ANALISIS PERAN LEVI STRAUSS & CO. DALAM MENYEBARKAN NILAI-NILAI IDEOLOGIS AMERIKA SERIKAT - Faiz Farisi; Umi O. Retnaningsih (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The company's activism got its name with the rising awareness of young consumers around the world. This new maneuver differs from traditional maneuvers such as corporate social responsibility and corporate political activity. One of the companies that has implemented this activism most intensively is Levi Strauss & Co. Through its rich history of American-inspired activism and corporate values, Levi Strauss & Co. has been recognized as a symbol of American culture. This study will discuss how the strategy carried out by Levi Strauss & Co. in spreading American cultural values. To answer the questions, the writer will analyze the documents from secondary data such as books, journals, news in newspapers, websites and other relevant data. The collected data will be processed using qualitative methods. This study uses Horkheimer's critical theory as a theoretical basis and Alexander Wendt's constructivism as a perspective. The results show that today's companies have more power, in their finances and marketing, to influence and shape society as desired. Trends/fashion adjustments are adapted to existing issues such as gender equality, democratic apathy, and armed violence. In this case, Levi Strauss & Co. as an American company that grew up based on American ideals has struggled to bring American society to life closer to their values such as equality and freedom.Keyword(s): Levi’s, LS & Co., american values, corporate activism